Put away your microscopes: the ependymoma molecular era has begun. Issue 6 (November 2017) - Mack, Stephen C.; Taylor, Michael D.
Abstract : Purpose of review: To synthesize, integrate, and comment on recent research developments to our understanding of the molecular basis of ependymoma (EPN), and to place this in context with current treatment and research efforts. Recent findings: Our recent understanding of the histologically defined molecular entity EPN has rapidly advanced through genomic, transcriptomic, and epigenomic profiling studies. Summary: These advancements lay the groundwork for development of future EPN biomarkers, models, and therapeutics. Our review discusses these discoveries and their impact on our clinical understanding of this disease. Lastly, we offer insight into clinical and research areas requiring further validation, and open questions remaining in the field.